(untitled) (Journal of Philosophy Culture and Political Science, 2018)
This paper considers potential negative implications of Kazakhstan’s pursuit of extensive Internet access. Specifically, we critically evaluate the following two concerns about the widespread availability of the Internet: a) that it will result in an erosion of traditional Kazakh culture and b) that an increase in time spent on-line will tend to produce individual isolation and thereby an increase in the incidence of cases of depression. With respect to the first concern, we make a prima facie case that several specific features of Kazakh culture make it particularly well-suited to absorb extensive access to the Internet without a resulting distortion or erosion of traditional Kazakh culture. With respect to the second concern, we note that the potential threat to psychological health posed by easy access to the Internet is significant and ought to be taken seriously, but we conclude that this threat is counterbalanced by other respects in which heightened access to the Internet can enhance mental health. Key words: intellectual capital, Internet, Islam, Kazakh culture, mental health